Khaki shadows - Arif, K. M. (Oxford University Press, 2001)
This book describes the powerful role of the army in the politics of Pakistan from its earliest years through the late 1990s and analyzes how political and military forces both created and undermined national prestige. Written by a regired general who held important positions in two different martial law administrations, it provides an insider's account of the intrigues, manipulations, and power struggles that engulfed Pakistan for much its history